Belajar Agama di Dusun Glagah Ombo: Antara Kebiasaan dan Kebutuhan - Syakuro, Muhammad Kifah Abdan (Maliki Interdisciplinary Journal, 2025)
Glagah Ombo Hamlet is a community with a strong religious tradition. The people in this hamlet have made religious learning a part of their daily lives through various activities such as regular religious studies, madrasa education, and commemoration of Islamic holidays. However, in the development of the times, religious learning is no longer just a habit, but has become a basic need to face various social and cultural challenges. This article discusses the pattern of religious learning in Glagah Ombo Hamlet, factors that influence religious awareness, challenges faced, and efforts that can be made to improve religious understanding in the community.